A method for preparing silicon-oxygen negative electrode material and its product

The preparation of silicon oxygen negative electrode materials through the centralized reaction and porous salt template deposition technology has solved the problems of low efficiency and poor circulation stability in the prior art for the first time, and achieved high capacity, high first efficiency and long circulation characteristics, and the process is environmentally friendly and low cost.

CN116282044BActive Publication Date: 2025-05-02ZHEJIANG LICHEN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310114566.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-01-13
Filing Date
2023-02-15
Publication Date
2025-05-02
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

The first-time Coulomb efficiency of existing silicon oxygen negative electrode materials is low, the cycle stability is poor, and the preparation process has problems with the use of harmful substances and high economic costs.

Method used

Silicon oxide gas is prepared by the middle reaction, and deposition is carried out using a porous salt template to form a porous silicon oxide powder precursor, and then silicon deposition and carbon coating are carried out to prepare a silicon oxygen negative electrode material with high capacity, high first efficiency and long cycle characteristics.

Benefits of technology

It has achieved high capacity, high first-time efficiency and long cycle characteristics, good conductivity, excellent rate performance, simple process, controllable, low industrial cost, green and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004078054240000151
    Figure BDA0004078054240000151
  • Figure BDA0004078054240000161
    Figure BDA0004078054240000161
Patent Text Reader

Abstract

The invention discloses a method for preparing a silicon-oxygen negative electrode material, comprising: using Si and SiO2 as raw materials, performing a neutralization reaction in a heating zone of a reaction device; introducing an inert gas into a condensation zone of the reaction device to fluidize a porous salt template powder placed in the condensation zone; introducing silicon dioxide gas obtained after the neutralization reaction into the condensation zone, and fully mixing it with the porous salt template powder in a fluidized state to obtain porous salt silicon dioxide powder; washing and removing the porous salt template to obtain a porous silicon dioxide powder precursor; and sequentially preparing the silicon-oxygen negative electrode material through a silicon deposition process and a carbon coating process. The silicon-oxygen negative electrode material prepared by the invention has high capacity, high first efficiency and long cycle characteristics, good electrical conductivity, and excellent rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a preparation method of a silicon-oxygen negative electrode material and a product thereof. Background Art

[0002] Silicon is considered to be the most promising candidate to replace graphite. It is the second most abundant element in the earth's crust, environmentally friendly, and has an ultra-high theoretical capacity (4200mAh / g). However, the drastic change in volume during the lithium insertion / extraction process has serious adverse consequences, resulting in very poor cycle stability. Although the volume expansion of silicon oxide materials during the lithium insertion process is greatly reduced compared to silicon alone, and it also has a high theoretical specific capacity (>2000mAh / g), the first coulombic efficiency of silicon oxide is too low (less than 76%), which limits its wider application; compared with the silicon-carbon products currently on the market, although the silicon-oxygen negative electrode has a lower first efficiency, its cycle life is much better than that of silicon-carbon products. Therefore, how to solve the problem of low first coulombic efficiency of silicon oxide has become the top priority of silicon-oxygen negative electrodes. Second-generation silicon-oxygen products generally use pre-lithiation or pre-magnesiation to solve the problem of low first coulombic efficiency. This solution significantly improves the first coulombic efficiency, but there will be some loss of capacity. The most important thing is that the economic cost pressure brought by the lithium and magnesium sources is unbearable for fields such as power batteries. At the same time, the product is highly alkaline, and there are great safety hazards and pollution risks in battery applications.

[0003] A Chinese patent document with publication number CN108923037A discloses a silicon-rich SiO x -C material and its preparation method and application, the method mentions that SiO2 is used as raw material, and SiO2@SiO@Si is generated by disproportionation reaction. x The material is then etched by HF to obtain a porous silicon-based material, and then Si is deposited inside the porous silicon-based material by CVD (chemical vapor deposition) to obtain silicon-rich SiO x The material is then deposited by CVD to form a carbon coating layer to produce silicon-rich SiO x -C material.

[0004] The technical solution claims that the prepared silicon-rich SiO x-C material has higher gram capacity and first coulombic efficiency than commercial SiO, and has relatively good cycle stability, overcoming the defect of low first efficiency of SiO. However, the preparation of porous silicon-based materials in this technical solution involves harmful substances such as hydrofluoric acid, and the acid etching method is used to form pores in silicon oxide from the outside to the inside. This method can form a larger specific surface area, but cannot form a higher pore volume, and thus cannot deposit and accommodate more nano-silicon particles, resulting in no significant change in the overall capacity. This can be confirmed by the first charge and discharge specific capacity data of the CR2016 button battery assembled from Example 1 and the comparative example given. In addition, the technical solution does not provide cycle stability data, and cannot support its claimed conclusion of good cycle stability. Summary of the Invention

[0005] In response to the above-mentioned problems existing in the prior art, the present invention discloses a method for preparing a silicon-oxygen negative electrode material, which has a simple and controllable preparation process, low industrial cost, and is green and pollution-free. The prepared negative electrode material has high capacity, high initial efficiency and long cycle characteristics, good conductivity, and excellent rate performance.

[0006] The specific technical solutions are as follows:

[0007] A method for preparing a silicon-oxygen negative electrode material comprises the following steps:

[0008] (1) Using Si and SiO2 as raw materials, a neutralization reaction is carried out in a heating zone of a reaction device; an inert gas is introduced into a condensation zone of the reaction device to fluidize a porous salt template powder placed in the condensation zone; silicon dioxide gas obtained after the neutralization reaction is introduced into the condensation zone and fully mixed with the porous salt template powder in a fluidized state to obtain a porous salt silicon dioxide powder;

[0009] The temperature of the condensation zone is 400-800°C;

[0010] (2) washing the porous salt silicon dioxide powder prepared in step (1) to neutrality, and drying to obtain a porous silicon dioxide powder precursor;

[0011] (3) subjecting the porous silicon oxide powder precursor prepared in step (2) to silicon deposition to obtain a pre-silicon silicon-oxygen composite material;

[0012] (4) The pre-silicon-silicon-oxygen composite material prepared in step (3) is carbon-coated and then post-processed to obtain the silicon-oxygen negative electrode material.

[0013] The present invention discloses a method for preparing a silicon-oxygen negative electrode material. Silicon oxide gas prepared by a neutralization reaction is used as a raw material, and porous salt is used as a deposition template for the silicon oxide gas. After sufficient mixing, porous salt silicon oxide powder is prepared. Then, the template is removed by simple washing to obtain a porous silicon oxide powder precursor with a rich pore structure and a high pore volume. Then, a silicon source is deposited to fill the pores of the porous silicon oxide powder precursor with silicon particles. Finally, carbon coating is performed to reduce the specific surface area. The prepared silicon-oxygen negative electrode material has high capacity, an initial efficiency reaching the level of pre-magnesium / pre-lithium silicon oxide, and a long cycle.

[0014] Experiments have found that if silicon oxide powder is used directly as raw material, mixed with porous salt template powder and then treated at high temperature, the porous silicon oxide powder precursor prepared has a very large specific surface area, but an extremely small pore volume. During the subsequent silicon deposition, it cannot accommodate a large number of nano-silicon particles, resulting in an excessively thick surface deposition layer, which leads to a serious deterioration in the cycle performance of the final assembled battery.

[0015] If the silicon dioxide gas prepared by the neutralization reaction is still used as the raw material, but no inert gas is introduced to make the porous salt template powder fluidized, it is impossible to successfully prepare a porous silicon dioxide powder precursor with a rich pore structure and a high pore volume, resulting in a serious deterioration in the cycle performance of the final assembled battery.

[0016] In step (1):

[0017] The porous salt template powder is selected from one or more of halogen salts, carbonates, sulfates, phosphates, aluminates, and silicates;

[0018] Preferably, the porous salt template powder is selected from halogen salts and carbonates, such as porous calcium carbonate template powder and porous sodium chloride template powder; more preferably, the porous calcium carbonate template powder is easy to prepare and has a larger adjustable range of specific surface area and pore volume.

[0019] The specific surface area of ​​the porous salt template powder is 500 to 2000 m 2 / g, pore volume is 0.4~1cm 3 / g; preferably, the specific surface area is 1000 to 2000m 2 / g, pore volume is 0.5~1.0cm 3 / g; More preferably, the specific surface area is 1500 to 2000m 2 / g, pore volume of 0.8~1.0cm 3 / g.

[0020] The deposition method in step (1) can ensure sufficient contact and deposition between the porous salt template powder and the silicon monoxide gas, and the pore volume of the prepared porous silicon monoxide powder precursor is close to the pore volume of the porous salt template powder; further experiments have found that the range of silicon deposition in step (3) is closely related to the pore volume of the porous silicon monoxide powder precursor; although the silicon deposition amount is controlled by the flow rate of the silicon source during the silicon deposition process and the temperature and time of the silicon deposition, the pore volume is different, and the appropriate silicon deposition amount matching it will be different, and the electrochemical performance of the battery assembled from the negative electrode material finally prepared will also change.

[0021] Preferably, the amount of silicon deposited in the pre-silicon-silicon-oxygen composite material is 35 to 90% of the absolute value of the pore volume of the porous silicon oxide powder precursor; more preferably, it is 60 to 75%.

[0022] The “absolute value” in the present invention refers to a numerical value without considering the unit.

[0023] The porous silicon oxide powder precursor has a pore volume of 0.8 cm 3 / g as an example, based on 35 to 90% of its absolute value, the appropriate silicon deposition amount is 28 to 72 wt%.

[0024] In step (1):

[0025] The inert gas is selected from one or more of nitrogen, argon, and helium, preferably nitrogen.

[0026] Preferably, the ratio of the absolute value of the inert gas flow rate to the absolute value of the mass of the porous salt template powder is 10 to 20:1; experiments have found that controlling the ratio between the two within the above range can ensure that the porous salt template powder is fully fluidized and reaches a "boiling" state, so that it can fully contact the silicon dioxide gas and achieve a better deposition effect.

[0027] Further experiments found that if the inert gas flow rate is too small or too large, it will affect the deposition effect of silicon dioxide gas, resulting in the pore volume of the porous silicon dioxide powder precursor prepared in step (2) being significantly smaller than the pore volume of the porous salt template powder used as the raw material, ultimately leading to the deterioration of the electrochemical performance of the assembled battery.

[0028] In this method, the temperature setting of the condensation zone is also crucial. This temperature will affect the specific surface area of ​​the prepared porous salt silicon oxide powder and the size of the silicon primary crystals of the silicon-oxygen negative electrode material finally prepared, thereby affecting the electrochemical performance of the final assembled battery. Experiments have found that if the temperature of the condensation zone is too high, the specific surface area of ​​the prepared porous salt silicon oxide powder will be too large. At the same time, the degree of disproportionation of silicon oxide in the condensation zone will deepen (this conclusion can be supported by XRD characterization), resulting in excessively large silicon primary crystals, which in turn leads to poor battery performance; too low a temperature will cause the deposition rate to increase, which will also affect the deposition effect. The temperature of the condensation zone is preferably 400-800°C, more preferably 600°C.

[0029] In step (1):

[0030] The temperature of the heating zone is 1300-1500°C;

[0031] The mass ratio of silicon dioxide gas to the porous salt template is 1 to 1.5:1.

[0032] The porous salt silicon oxide powder prepared in step (1) has a particle size D50 < 20 μm, a particle size concentration SPAN value less than 1.5, and a specific surface area ≤ 5m 2 The powder is then subjected to roller crushing, jaw crushing, pulverization, and sieving. Based on the performance of the assembled battery, the D50 of the porous salt silicon oxide powder after sieving is controlled to be 6 to 8 μm.

[0033] In step (2):

[0034] The washing process is to remove the porous salt template in the porous salt silicon oxide powder. If the type of porous salt template used is a halogen salt, such as a porous sodium chloride template, it can be directly washed with water; if the type of porous salt template used is a carbonate, such as a porous calcium carbonate template, first use a dilute acid, such as dilute hydrochloric acid, to wash and remove the template, and then wash with water until neutral.

[0035] In step (3):

[0036] The silicon deposition is carried out by conventional deposition methods in the art, and the specific process will not be described in detail.

[0037] The silicon source used in the silicon deposition is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; the silicon source flow rate is 1 to 50 L / min;

[0038] The silicon deposition temperature is 400-800°C, and the time is 0.5-12 hours.

[0039] Preferred:

[0040] The silicon deposition amount in the pre-siliconized silicon-oxygen composite material is 40 to 75 wt%;

[0041] Further preferred:

[0042] The specific surface area of ​​the porous salt template powder is 1500 to 2000 m 2 / g, pore volume of 0.8~1.0cm 3 / g;

[0043] The silicon deposition amount in the pre-siliconized silicon-oxygen composite material is 50-60 wt%.

[0044] More preferably:

[0045] The specific surface area of ​​the porous salt template powder is 1500m 2 / g, pore volume is 0.8cm 3 / g.

[0046] With the continuous optimization of the above process parameters, the amount of silicon deposition in the pre-silicon-silicon-oxygen composite material is appropriate and matches the pore volume of the porous silicon oxide powder precursor. The battery finally assembled has high capacity, high initial efficiency and high cycle stability.

[0047] In step (4):

[0048] The carbon coating includes one or more of gas phase carbon coating, liquid phase carbon coating, and solid phase carbon coating; the specific coating process adopts conventional operations in this field.

[0049] Preferred:

[0050] The gas phase carbon coating adopts hydrocarbon gas as carbon source;

[0051] The liquid phase carbon coating uses a carbon-containing high molecular polymer as a carbon source;

[0052] The solid phase carbon coating uses asphalt as the carbon source;

[0053] The carbon coating temperature is 400-1000° C., and the time is 0.5-12 hours.

[0054] Preferably, the carbon content in the silicon-oxygen negative electrode material prepared after carbon coating is 2 to 8 wt %, more preferably 3 to 5 wt %.

[0055] The post-processing includes one or more of breaking up, screening and demagnetization.

[0056] The present invention also discloses a silicon-oxygen negative electrode material prepared according to the above method, comprising a porous silicon oxide powder precursor, nano-silicon particles deposited in the pores, and an outermost carbon layer.

[0057] Preferred:

[0058] The specific surface area of ​​the silicon-oxygen negative electrode material is less than 10m 2 / g, more preferably less than 3m 2 / g;

[0059] The resistivity of the silicon-oxygen negative electrode material is less than 10Ω / cm 2 , more preferably less than 0.75Ω / cm 2 ;

[0060] The silicon primary crystal grains of the silicon-oxygen negative electrode material are less than 30 nm, and more preferably less than 10 nm;

[0061] The thickness of the outermost carbon layer of the silicon-oxygen negative electrode material is preferably 5 to 50 nm, more preferably 10 to 30 nm.

[0062] Experiments have shown that the silicon-oxygen negative electrode material prepared by the above method has high capacity, high initial efficiency and long cycle characteristics, good conductivity and excellent rate performance.

[0063] Compared with the prior art, the present invention has the following advantages:

[0064] The present invention discloses a method for preparing a silicon-oxygen negative electrode material. Natural porous silicon oxide is prepared by a porous salt template, which ensures the uniform dispersion of silicon clusters and silicon dioxide clusters in the silicon oxide and the cyclic stability of the silicon oxide itself. The porous salt template is removed by washing, and the process is green and pollution-free. Then, silicon is deposited and the pore structure characteristics of the prepared porous silicon oxide are utilized to adsorb and crack the silicon source gas, which can be uniformly deposited and cracked. Finally, carbon coating is used to reduce the specific surface area. At the same time, the carbon layer has the characteristics of improving ionic conductivity and electronic conductivity. DETAILED DESCRIPTION

[0065] The specific implementation method of the present invention is further described below with reference to examples. It should be noted that the specific implementation method described here is only for illustrating and explaining the present invention and is not intended to limit the scope of protection of the present invention.

[0066] The raw materials or reagents used in the present invention are all purchased from mainstream manufacturers in the market. Those without indicating the manufacturer or those without indicating the concentration are all raw materials or reagents of analytical grade that can be routinely obtained. As long as the desired effect can be achieved, there are no particular restrictions. The instruments and equipment such as the stirrer, coating machine, drying equipment, and thickness gauge used in the present embodiment are all purchased from major manufacturers in the market. As long as the desired effect can be achieved, there are no particular restrictions. In the present embodiment, those without indicating the specific technology or conditions are carried out according to the technology or conditions described in the literature in this area or according to the product specifications.

[0067] Example 1

[0068] (1) 800 g of Si and 800 g of SiO2 were added to the heating zone of the sintering furnace and heated to 1350°C for a neutralization reaction. The reaction yield was 90% (the following examples were all calculated based on this yield); 1 kg of porous calcium carbonate template powder (with a specific surface area of ​​1500 m 2 / g, pore volume of 0.8cm 3 / g) was placed in a condensation zone of a sintering furnace and heated to 600°C. Nitrogen was then introduced into the condensation zone at a flow rate of 15 L / min; the nitrogen to be introduced fluidized the porous calcium carbonate template powder, and silicon dioxide gas prepared by the neutralization reaction was then introduced into the condensation zone to uniformly deposit the silicon dioxide gas in the porous calcium carbonate template powder. After cooling, the powder was taken out and subjected to roller crushing, jaw crushing, pulverization, and sieving to obtain a porous calcium carbonate silicon dioxide powder with a D50 of 6 μm. The specific surface area thereof is listed in Table 1 below;

[0069] (2) The porous calcium carbonate template in the porous calcium carbonate silicon oxide powder was cleaned with dilute hydrochloric acid at 60° C., then washed with deionized water until neutral, and dried to obtain a porous silicon oxide powder precursor. The pore volume thereof is listed in Table 1 below.

[0070] (3) 1 kg of porous silicon oxide precursor powder was added to a CVD furnace, monosilane gas was introduced at a flow rate of 10 L / min, and deposition was carried out at 500° C. for 5 h to prepare a pre-silicon silicon-oxygen composite material, in which the silicon deposition amount in the composite material was 60 wt%;

[0071] (4) 1 kg of pre-siliconized silicon-oxygen composite negative electrode material was added to a CVD furnace, and acetylene gas was introduced at a flow rate of 1 L / min under a nitrogen atmosphere. Carbon coating was performed by deposition at 900 ° C for 2 h, and the carbon coating amount was 3% (based on the product). After being dispersed, sieved, and demagnetized, the silicon-oxygen negative electrode material was obtained.

[0072] Comparative Example 1

[0073] (1) 1.4 kg of silicon oxide powder and 1 kg of porous calcium carbonate template powder (specific surface area of ​​1500 m 2 / g, pore volume of 0.8cm 3 / g) were uniformly mixed, placed in a sintering furnace, heated to 600°C, maintained for sufficient reaction time, cooled, taken out, and subjected to roller crushing, jaw crushing, pulverization, and sieving to obtain a porous calcium carbonate and silicon oxide powder mixture with a D50 of 6 μm. The specific surface area thereof is listed in Table 2 below;

[0074] (2) The product prepared in step (1) was then washed with dilute hydrochloric acid at 60° C., and then washed with deionized water until neutral, and dried to prepare a porous silicon oxide powder precursor, the pore volume of which is listed in Table 2 below;

[0075] Steps (3) to (4) are exactly the same as those in Example 1.

[0076] Comparative Example 2

[0077] The preparation process is basically the same as that of Example 1, except that nitrogen is not introduced in step (1) to fluidize the porous calcium carbonate template powder.

[0078] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this comparative example are listed in Table 2 below.

[0079] Comparative Example 3: Preparation of porous silicon oxide powder precursor with reference to the technical solution in CN108923037A

[0080] (1) 1 kg of SiO powder was placed in a sagger, and then placed in a tube furnace in an argon protective atmosphere. The tube furnace was heated to 900 °C at a heating rate of 5 °C / min, kept at this temperature for 2 h, and the prepared SiO was taken out after cooling. x . SiO x and a 40% by mass HF aqueous solution in a mass ratio of 2:1, soaked for 0.5 h, then filtered, washed three times with deionized water until the washing liquid was neutral, and then placed in a vacuum drying oven with a vacuum degree of -0.8 MPa and dried at 80°C to obtain a porous silicon-based material, which was recorded as a porous silicon oxide powder precursor;

[0081] (2) The silicon deposition process is exactly the same as step (3) in Example 1;

[0082] (3) The carbon coating process is exactly the same as step (4) in Example 1.

[0083] The pore volume of the porous silicon 2 oxide powder precursor prepared in this comparative example is listed in Table 2 below.

[0084] Example 2

[0085] The preparation process is basically the same as that of Example 1, except that:

[0086] In step (1), the specific surface area of ​​the porous calcium carbonate template powder used is 1200m 2 / g, pore volume of 0.6cm 3 / g;

[0087] In step (3), the silicon deposition time is replaced with 3 hours, and the silicon deposition amount in the prepared pre-siliconized silicon-oxygen composite material is 40 wt%.

[0088] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0089] Example 3

[0090] The preparation process is basically the same as that of Example 1, except that:

[0091] In step (1), the specific surface area of ​​the porous calcium carbonate template powder used is 1000m 2 / g, pore volume of 0.5cm 3 / g;

[0092] In step (3), the silicon deposition time is replaced with 2.5 h, and the silicon deposition amount in the prepared pre-siliconized silicon-oxygen composite material is 30 wt%.

[0093] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0094] Example 4

[0095] The preparation process is basically the same as that of Example 1, except that:

[0096] In step (1), the specific surface area of ​​the porous calcium carbonate template powder used is 2000m 2 / g, pore volume is 1.0cm 3 / g;

[0097] In step (3), the silicon deposition time is replaced with 6.2 h, and the silicon deposition amount in the prepared pre-siliconized silicon-oxygen composite material is 75 wt %.

[0098] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0099] Example 5

[0100] The preparation process is basically the same as that of Example 1, except that in step (1), the condensation zone is heated to 400°C.

[0101] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0102] Example 6

[0103] The preparation process is basically the same as that of Example 1, with the only difference being that in step (1), the condensation zone is heated to 800°C.

[0104] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0105] Example 7

[0106] The preparation process is basically the same as that of Example 1, except that in step (1):

[0107] Replace the mass of Si and SiO2 with 550g;

[0108] The nitrogen flow rate into the condensation zone was changed to 10 L / min.

[0109] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0110] Example 8

[0111] The preparation process is basically the same as that of Example 1, except that in step (1):

[0112] Replace the mass of Si and SiO2 with 830g;

[0113] The nitrogen flow rate into the condensation zone was changed to 20 L / min.

[0114] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0115] Example 9

[0116] The preparation process is basically the same as that of Example 1, with the only difference being that in step (3), the silicon deposition time is replaced with 6 h, and the silicon deposition amount in the prepared pre-siliconized silicon-oxygen composite material is 72 wt%.

[0117] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0118] Example 10

[0119] The preparation process is basically the same as that of Example 1, except that in step (3), the silicon deposition time is replaced with 4.1 h, and the silicon deposition amount in the prepared pre-siliconized silicon-oxygen composite material is 50 wt%.

[0120] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0121] Example 11

[0122] The preparation process is basically the same as that of Example 1, except that in step (3), the silicon deposition time is replaced with 2.5 h, and the silicon deposition amount in the prepared pre-siliconized silicon-oxygen composite material is 30 wt%.

[0123] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this example are listed in Table 1 below.

[0124] Comparative Example 4

[0125] The preparation process is basically the same as that of Example 1, with the only difference being that in step (1), the condensation zone is heated to 1000°C.

[0126] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this comparative example are listed in Table 2 below.

[0127] Comparative Example 5

[0128] The preparation process is basically the same as that of Example 1, except that in step (1), the nitrogen flow rate introduced into the condensation zone is replaced with 5 L / min.

[0129] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this comparative example are listed in Table 2 below.

[0130] Comparative Example 6

[0131] The preparation process is basically the same as that of Example 1, except that in step (1), the nitrogen flow rate introduced into the condensation zone is replaced with 25 L / min.

[0132] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this comparative example are listed in Table 2 below.

[0133] Comparative Example 7

[0134] The preparation process is basically the same as that of Example 1, except that in step (3), the silicon deposition time is replaced with 7.5 h, and the silicon deposition amount in the prepared pre-siliconized silicon-oxygen composite material is 90 wt%.

[0135] The specific surface area of ​​the porous calcium carbonate silicon oxide powder and the pore volume of the porous silicon oxide powder precursor prepared in this comparative example are listed in Table 2 below.

[0136] Battery preparation:

[0137] Under a nitrogen atmosphere, the conductive agent SuperP and sodium carboxymethyl cellulose (CMC) were thoroughly mixed and dispersed with deionized water. The negative electrode materials prepared in the above examples or comparative examples were then added and stirred at 2000 rpm for 10 minutes. A water-based binder AONE (purchased from Shenzhen Yanyi New Materials Co., Ltd.) was then added and stirred at 2000 rpm for 10 minutes to obtain a negative electrode slurry. The mass ratio of the negative electrode material, conductive agent SuperP, sodium carboxymethyl cellulose (CMC), and binder AONE (by dry weight) was 70:15:5:10, and the solid content of the slurry was 15 wt%.

[0138] The negative electrode slurry was coated on the current collector copper foil, dried at 80 ° C for 30 min under a relative vacuum of -0.1 MPa, and then roller pressed at room temperature. The surface density was 9.1 mg / cm 2 , then punched and cut into discs with a diameter of 14 mm to make electrode plates.

[0139] The counter electrode was a lithium sheet CR2016 (purchased from Shenzhen Yongxingye Equipment Technology Co., Ltd.) with a diameter of 16 mm.

[0140] The button cells were assembled in a glove box under an argon atmosphere, with moisture and oxygen levels below 0.01 ppm. The assembly sequence was "negative electrode shell - gasket - lithium sheet - electrolyte - separator - electrolyte - electrode sheet - positive electrode shell." The electrolyte consisted of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1), containing 1.0 M LiPF6.

[0141] The diameter of the electrode plate is 14mm, the diameter of the lithium plate is 16mm, the diameter of the diaphragm is 19mm, and the size of the battery shell (positive and negative shells) is 20mm. The diaphragm is a 12μm thick ceramic coated isolation membrane (purchased from Shanghai Enjie New Materials Technology Co., Ltd.). The assembled button battery is placed in the mold groove of a hydraulic sealing machine (purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), locked, and pressurized >500kg / cm 2 , then unlock it and take out the sealed button battery.

[0142] The following methods were used to characterize the batteries assembled with the negative electrode materials prepared in Examples 1 to 11 and Comparative Examples 1 to 7, respectively.

[0143] Performance testing:

[0144] Phase analysis was performed using Bruker's XRD-D2 PHASER, and calculations were performed using the Scherrer formula to test silicon primary grains.

[0145] The morphology test was performed using the Thermo Fisher Phenom Generation 5 from the United States;

[0146] The specific surface area was tested using an American Micrometer fully automatic specific surface area analyzer;

[0147] The powder resistance was tested using a lattice powder resistivity tester with a four-probe method;

[0148] The battery cycle performance was tested on the Blue Power Battery Test System CT2001A equipment.

[0149] At 25°C, the charge and discharge cycle characteristics of the button battery were tested using the above-mentioned blue electric test cabinet. First, discharge to 0.005V at 0.1C, then discharge to 0.001V at 0.08C, discharge to 0.001V at 0.05C, discharge to 0.001V at 0.02C, and let it stand for 10 minutes. Then charge to 1.5V at 0.1C, let it stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, and calculate the capacity retention rate after 100 cycles. The test and calculation process of the capacity retention rate after 500 cycles adopt the same method. The test results are shown in Tables 1 and 2 below.

[0150] Table 1

[0151]

[0152] 1 is the specific surface area of ​​porous salt silicon oxide powder;

[0153] 2 is the pore volume of the porous silicon oxide powder precursor;

[0154] 3 is the specific surface area of ​​the silicon-oxygen negative electrode material.

[0155] Table 2

[0156]

[0157] By comparing the data of Examples 1 to 4, it can be found that the pore volume and specific surface area of ​​porous silicon oxide formed by porous salt templates with different pore volumes and specific surface areas are also different, and the capacity, first efficiency and cycle stability data of the finally assembled battery are also different. Therefore, by screening the appropriate pore volume size to obtain the appropriate silicon deposition amount, it is possible to take into account both the capacity and first efficiency while ensuring the cycle performance.

[0158] By comparing Examples 1 and 9 to 10, it can be found that the amount of silicon deposition within a suitable range is helpful to improve the capacity and the first coulomb efficiency. At the same time, the silicon primary grains will not be particularly large, which slows down the volume expansion and effectively improves the capacity retention rate of the cycle; by comparing Example 1 and Example 11, it can be found that a slightly lower deposition amount, although it effectively improves the capacity retention rate of the cycle, is easy to affect the capacity and the first efficiency is low. Compared with the pre-magnesium and pre-lithium products, the first efficiency is low and the market prospect is poor; by comparing Example 1 and Comparative Example 7, it can be found that excessive deposition can easily lead to the formation of a shell layer of silicon particles on the surface of silicon monoxide, which is easy to crack after rolling and other chemical steps. In addition, the volume expansion leads to an incomplete coating layer, so the side reactions of the electrolyte continue to proceed and be consumed, resulting in poor cycle and serious capacity decay.

[0159] By comparing Examples 1, 5, and 6 with Comparative Example 4, it can be found that regulating the temperature of the condensation zone will affect the specific surface area of ​​the prepared porous salt silicon oxide powder and the size of the silicon primary crystals, thereby affecting the electrochemical performance of the final assembled battery. Analysis shows that the reason may be that the temperature of the condensation zone will affect the contact degree between the silicon oxide gas and the porous salt template powder, the deposition effect of silicon oxide, and the self-disproportionation degree of silicon oxide; relatively high temperatures affect the contact degree between the silicon oxide gas and the porous salt template powder, so the specific surface area of ​​the porous salt silicon oxide powder prepared in Example 6 is larger than that in Example 1; too high a temperature can easily lead to an excessively large specific surface area; at the same time, the degree of disproportionation is deepened, resulting in excessively large silicon primary crystals, which in turn leads to poor battery performance; too low a temperature will cause the deposition rate to become faster, which also affects the deposition effect. Therefore, the temperature of the condenser can be selected from 400 to 800°C, but the optimal temperature is 600°C.

[0160] By comparing Examples 1 and 7 to 8, it can be found that the nitrogen purge flow rate within the appropriate range can make the porous salt template fully fluidized in the condensation zone and reach a "boiling" state, so that it can fully contact the silicon dioxide gas, achieve a better deposition effect, and ensure product quality; by comparing Example 1 with Comparative Examples 5 to 6, it can be found that an inappropriate amount of nitrogen will cause the cycle stability of the final assembled battery to deteriorate significantly. The reason for this may be that: too low a nitrogen amount cannot fluidize the porous salt template, resulting in uneven deposition and excessive deposition, which affects the pore volume and specific surface area of ​​the porous silicon dioxide, and further causes the reasonable silicon deposition amount to become excessive, thereby affecting the battery performance; and too high a nitrogen flow rate cannot make the silicon dioxide gas fully contact the porous salt template, resulting in the deposition of silicon dioxide itself, and unable to form pores and generate pore volume. When silicon is deposited, it is deposited on the surface, so the cycle performance is poor.

[0161] By comparing Example 1 with Comparative Example 1, it can be found that the cycle performance of the battery assembled in Comparative Example 1 is seriously deteriorated, which is far lower than that of Example 1. The reason for this may be that the simple blending of porous salt and silicon dioxide powder cannot achieve the purpose of pore formation. Therefore, the prepared product is only a mixture of porous calcium carbonate and silicon dioxide powder, which has a large specific surface area, mainly contributed by the porous salt. Silicon dioxide itself does not have a large pore volume and specific surface area. Therefore, when silicon is deposited, it cannot accommodate more nano-silicon particles, resulting in an excessively thick surface deposition layer, which leads to serious deterioration of the cycle.

[0162] By comparing Example 1 with Comparative Example 2, it can be found that the cycle performance of the battery assembled in Comparative Example 2 deteriorates and is much lower than that in Example 1. The reason for this may be that when the porous salt template powder is not fluidized and boiled with nitrogen, it cannot fully contact with the silicon dioxide gas. Only the part that contacts earlier can be deposited into the pores, and the other parts are deposited as pure silicon dioxide to form silicon dioxide blocks, which cannot form a higher pore volume and rich pore structure. Similarly, when silicon is deposited, most of it is deposited on the surface to form a thick silicon layer, which expands severely and has poor circulation.

[0163] By comparing Example 1 with Comparative Example 3, it can be found that the cycle performance of the battery assembled in Comparative Example 3 deteriorates and is much lower than that in Example 1. The reason for this may be that when the porous silicon monoxide prepared by the acid etching method is used as the substrate, the primary silicon grains are too large and the disproportionation is relatively serious, so the volume effect is more obvious, which easily leads to too fast cycle attenuation and has limitations in application.

[0164] The above description is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. The above description of the present invention using specific examples is only used to help understand the present invention and is not intended to limit the present invention. Those skilled in the art of the present invention can also make several simple deductions, modifications, substitutions or combinations based on the concept of the present invention. These deductions, modifications, substitutions or combinations also fall within the scope of the claims of the present invention.

Claims

1. A method for preparing a silicon-oxygen negative electrode material, characterized in that: The steps include: (1) Using Si and SiO2 as raw materials, a neutralization reaction is carried out in a heating zone of a reaction device; an inert gas is introduced into a condensation zone of the reaction device to fluidize a porous salt template powder placed in the condensation zone; silicon dioxide gas obtained after the neutralization reaction is introduced into the condensation zone and fully mixed with the porous salt template powder in a fluidized state to obtain a porous salt silicon dioxide powder; The porous salt template powder is selected from porous calcium carbonate template powder; The temperature of the condensation zone is 400-800°C; (2) washing the porous salt silicon dioxide powder prepared in step (1) to neutrality, and drying to obtain a porous silicon dioxide powder precursor; (3) subjecting the porous silicon oxide powder precursor prepared in step (2) to silicon deposition to obtain a pre-silicon silicon-oxygen composite material; (4) The pre-silicon-silicon-oxygen composite material prepared in step (3) is carbon-coated and then post-treated to obtain the silicon-oxygen negative electrode material.

2. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (1): The specific surface area of ​​the porous salt template powder is 500-2000 m 2 / g, pore volume is 0.4~1 cm 3 / g; The inert gas is selected from one or more of nitrogen, argon and helium; The ratio of the absolute value of the inert gas flow rate to the absolute value of the mass of the porous salt template powder is 10-20:

1.

3. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (1): The specific surface area of ​​the porous salt template powder is 1000-2000 m 2 / g, pore volume is 0.5~1.0 cm 3 / g.

4. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (1): The temperature of the condensation zone is 600°C; The specific surface area of ​​the porous salt template powder is 1500-2000 m 2 / g, pore volume is 0.8~1.0 cm 3 / g.

5. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (1): The temperature of the heating zone is 1300-1500°C; The mass ratio of silicon dioxide gas to the porous salt template is 1-1.5:

1.

6. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (1), the prepared porous salt silicon dioxide powder is subjected to roller, jaw crusher, pulverizing and screening treatments.

7. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (3): The silicon source used for the silicon deposition is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; The silicon deposition amount in the pre-siliconized silicon-oxygen composite material is 40-75 wt%.

8. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (3), the amount of silicon deposited in the pre-siliconized silicon-oxygen composite material is 50-60 wt%.

9. The method for preparing the silicon-oxygen negative electrode material according to claim 1, characterized in that: In step (4): The carbon coating includes one or more of gas phase carbon coating, liquid phase carbon coating, and solid phase carbon coating; The carbon content in the silicon-oxygen negative electrode material prepared after carbon coating is 2~8 wt%; The post-processing includes one or more of breaking up, screening and demagnetization.

10. A silicon-oxygen negative electrode material prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silicon-rich SiOx-C material and preparation method and application thereof

    CN108923037A

  • Preparation method of long-circulation silicon monoxide / carbon composite negative electrode material

    CN110828786A

  • Lithium ion battery negative electrode material and preparation method thereof

    CN111430692A